Molecular phylogeny and genetic diversity of domestic yaks (Bos grunniens) in Pakistan based on mitochondrial and microsatellite markers - Hussain, Tanveer (Array, 2021)
The complete Cytchrome b gene and partial mtDNA control region were sequenced for the Pakistani domestic yak (Bos grunniens) within the Bovidae family. A total of 300 samples were genotyped using 27 bovine microsatellite markers from the Gilgit-Baltistan and Skardu regions of Pakistan. We identified a total of 35 mutations and 9 haplotypes based on D-loop sequences, with a haplotype and nucleotide diversity of 0.9640±0.051 and 0.02172±0.00224, respectively. For the Cyt b gene, a total of 23 variable sites and six different haplotypes were observed with 0.885±0.067 haplotype and 0.00989±0.003 nucleotide diversity. Phylogenetic analysis of D-loop and Cyt b gene suggested that domestic yak sequences cluster into two highly divergent maternal lineages (lineages I and II), while three haplogroups A, C, and D were identified of the six previously known haplogroups. Haplogroups A and C were dominant and widely distributed among all investigated yak samples. All microsatellites were polymorphic and a total of 138 alleles were observed, with average polymorphic information content (PIC) of 0.56 indicating their effectiveness. The average heterozygosity was observed at 0.6071 with allele diversity of 5.1111 and gene diversity of 0.4830. The implications of these findings can be applied for yak conservation.